1993
DOI: 10.1002/art.1780360604
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of giant cell arteritis

Abstract: The actinic hypothesis generates more heat than lightIn a recent Current Comment published in Arthritis and Rheumatism (l), O'Brien and Regan review their concept of the pathogenesis of giant cell arteritis (GCA) and emphasize their commitment to the ''actinic hypothesis." This hypothesis proposes that the primary causative lesion in GCA is an alteration or degeneration of the elastic lamina of the temporal artery caused by solar radiation. O'Brien and Regan believe the degenerated elastin then triggers the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…Both are much more common in whites than in other racial or ethnic groups (105). Prevalence in the US also tends to be highest in populations of northern European descent (106). PMR and GCA are likely to represent 2 manifestations of a single disease process (107).…”
Section: Resultsmentioning
confidence: 99%
“…Both are much more common in whites than in other racial or ethnic groups (105). Prevalence in the US also tends to be highest in populations of northern European descent (106). PMR and GCA are likely to represent 2 manifestations of a single disease process (107).…”
Section: Resultsmentioning
confidence: 99%
“…There are existing data suggesting that this may relate to human leucocyte antigen (HLA) type. An increased frequency of HLA-DR4 in patients with GCA has been described 17. It has also been demonstrated that HLA-DRB1*0401 and HLA-DRB1*0404, which are alleles that are components of the DR4 gene, are less frequent in the Japanese population 18.…”
Section: Discussionmentioning
confidence: 96%
“…This hypothesis is supported by histopathologic findings indicating a dense cellular infiltrate in the internal elastic lamina and disintegration of the elastic tissue (3,4,13). Mechanisms such as sun exposure (1,12,45) and compression by tight-fitting headwear have been implicated in alteration and degeneration of elastic fibers, which could then result in autosensitization. m e IV collagenases degrade elastin with remarkable efficiency (14), and they can also degrade other components of basement membranes (18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%